2021
DOI: 10.1108/emjb-03-2021-0041
|View full text |Cite
|
Sign up to set email alerts
|

Authenticity as an antecedent of brand image in a positive emotional consumer relationship: the case of craft beer brands

Abstract: PurposeThis study, based on craft beer brands, aims (1) to explain the importance of four brand authenticity dimensions (continuity, originality, reliability and naturalness) in consumers' perceptions of brand image; (2) to verify if the brand–consumer emotional relationship (brand love) is enhanced by the consumer's perceptions of the brand's image; (3) to verify if the consumer's perceptions of the brand's image increase brand satisfaction; and (4) to verify if brand satisfaction increases brand love.Design/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 94 publications
0
7
0
3
Order By: Relevance
“…H5a and H5b demonstrated that the interaction effects of perceived brand authenticity and brand image significantly impacted perceived brand loyalty in terms of brand trust while having no effect on consumers’ PWOM toward global brands. A positive brand image contributes positively to a brand’s authenticity (Rodrigues et al , 2021). Thus, an authentic brand image can assist companies in achieving competitive advantages by fostering consumer trust in brands (Napoli et al , 2014; Schallehn et al , 2014).…”
Section: Discussion and Theoretical Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…H5a and H5b demonstrated that the interaction effects of perceived brand authenticity and brand image significantly impacted perceived brand loyalty in terms of brand trust while having no effect on consumers’ PWOM toward global brands. A positive brand image contributes positively to a brand’s authenticity (Rodrigues et al , 2021). Thus, an authentic brand image can assist companies in achieving competitive advantages by fostering consumer trust in brands (Napoli et al , 2014; Schallehn et al , 2014).…”
Section: Discussion and Theoretical Contributionsmentioning
confidence: 99%
“…Thus, authenticity is associated with a person who is real and authentic to his or her own identity in order to confront external incidents (Safeer et al, 2021b;Schallehn et al, 2014). Likewise, authenticity assessment is primarily based on consumers' perceptions (Rose and Wood, 2005) and consumer perceptions are essential when evaluating the authenticity of CSR initiatives and global brands (Moehl and Friedman, 2021;Fatma and Khan, 2022;Safeer et al, 2021b).…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Brand Image. Brand image telah digambarkan sebagai suatu hal yang penting untuk mengidentifikasi bagaimana perasaan konsumen terhadap brand dan hubungan positif mereka di dalamnya (Rodrigues et al, 2021).…”
Section: Tinjauan Pustakaunclassified
“…Dalam bersaing dengan banyaknya brand sejenis, pelaku usaha atau bisnis perlu membangun brand image. Brand image telah digambarkan sebagai suatu hal yang penting untuk mengidentifikasi bagaimana perasaan konsumen terhadap brand dan hubungan positif mereka di dalamnya (Rodrigues et al, 2021). Oleh karena itu, penting bagi pelaku usaha menciptakan sebuah brand image yang baik di mata konsumen.…”
unclassified
“…Por lo tanto, la imagen de marca es un factor relevante al momento de generar emociones lo cual se traduce en un amor de marca (Rodrigues et al, 2021), es por ello que los consumidores identifican a la marca por los beneficios o atributos que esta les represente (Ceyhan & Yozgat, 2021).…”
Section: Introductionunclassified